The Results of the Study of Human Anomalous Thermal Fields Under Irradiation - Glushchuk, M.I.; Gordiyenko, E.Yu.; Fomenko, Yu.V.; Shustakova, G.V.; Miroshnichenko, L.G.; Kolotilov, N.N. (Science and Innovation, 2024)
The results of thermal imaging study of thermal fields on the skin surface of cancer patients treated with radiotherapy have been presented. Quantitative and statistical approach to the analysis of thermal images has been described. The results of thermal survey of patients before the start of irradiation have showed that thermal imaging diagnostics of the majority of internal tumors is limited or even impossible. However, the obtained correlation coefficients R = 0.76÷0.81 between the thermal parameters and the clinical side toxic reaction indicators, as well as the resulting «good quality» parameter of prognosis method have proved the possibility of using the thermal imaging method for monitoring and prediction of side toxic reactions of radiation therapy. The necessity of increasing the statistical power of the analyzed samples has been noted.